Integrating ABCD, SLA, and TALC in Tamansari Tourism Village Development - Panca Oktawirani; Warda Ayu Berliana Nafis (E-Journal of Tourism, 2026)
This study integrates the Asset-Based Community Development (ABCD) and Sustainable Livelihood Approach (SLA) frameworks to provide a holistic understanding of community-based tourism in the Tamansari tourism village, Banyuwangi. Data were collected through in-depth interviews with 12 informants, including representatives from Village-Owned Enterprises (BUMDes), five local MSMEs, and two tourism attraction managers, supported by document analysis of revenue and visitor statistics. To enhance measurability, the study applies the OSOI framework, which analyzes asset categories in tourism development. Five asset categories were assessed: natural (82%), human (84%), social (92%), physical (72%), and financial (68%). The findings highlight three key pillars driving the tourism village: Tamansari BUMDes, Lunyau Coffee agrotourism, and Sendang Seruni spiritual tourism. These entities play significant roles in organizing tourism activities and fostering community participation. Based on the Tourism Area Life Cycle (TALC) concept, Tamansari Tourism Village is currently in the development stage, characterized by infrastructure expansion and institutional strengthening. This study demonstrates that qualitative data can be transformed into quantifiable indicators, offering a more structured evaluation approach. Furthermore, the integration of ABCD, SLA, and TALC provides a novel analytical framework. ABCD provides the lens for asset mobilization, SLA evaluates the sustainability of livelihood outcomes, and TALC situates these processes within the temporal dynamics of destination development. It contributes to the theoretical advancement of community capability frameworks, particularly in strengthening local institutions and promoting livelihood diversification. While context-specific, this approach offers insights Although the findings are context-specific, this approach offers practical insights for future comparative studies on sustainable tourism village development.